2011
DOI: 10.1002/jnr.22748
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinase activation precedes NADPH oxidase‐dependent damage in neurons exposed to the proinflammatory cytokine tumor necrosis factor‐α

Abstract: Inflammation accompanied by severe oxidative stress plays a vital role in the orchestration and progression of neurodegeneration prevalent in chronic and acute CNS pathologies as well as in aging. The proinflammatory cytokine tumor necrosis factor alpha (TNFα) elicits the formation of the bioactive ceramide by stimulating the hydrolysis of the membrane lipid sphingomyelin by sphingomyelinase activities. Ceramide stimulates the formation of reactive oxygen species (ROS) and apoptotic mechanisms in both neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 48 publications
(61 reference statements)
1
38
0
1
Order By: Relevance
“…Neutral sphingomyelinase 2 (nSMase2, product of the SMPD3 gene) is the major neutral sphingomyelinase (N-SMase) in mammalian cells for the stressinduced generation of ceramide (4). TNF-α (9-15), cell confluence (16,17), oxidative stress (18)(19)(20), and inflammation (20,21) are all potent activators of nSMase2.…”
mentioning
confidence: 99%
“…Neutral sphingomyelinase 2 (nSMase2, product of the SMPD3 gene) is the major neutral sphingomyelinase (N-SMase) in mammalian cells for the stressinduced generation of ceramide (4). TNF-α (9-15), cell confluence (16,17), oxidative stress (18)(19)(20), and inflammation (20,21) are all potent activators of nSMase2.…”
mentioning
confidence: 99%
“…2 and Table 1) (Du et al 2012). Lastly, TNF-α was shown to negatively regulate SK/S1P signaling via promotion of NADPH oxidase (Nox)-mediated oxidative damage to SK1 in neuronal cells (Barth et al 2012). Discussed in the next chapter, the SK/S1P pathway has been shown to mediate a large portion of TNF-α-mediated events, supporting TNF-α induced "inside-out" S1P signaling.…”
Section: Tumor Necrosis-alpha (Tnf-α)mentioning
confidence: 97%
“…On the other hand, C1P has been demonstrated to mediate inflammatory responses (Chalfant and Spiegel 2005;HinkovskaGalcheva et al 2005) and to promote cell migration Granado et al 2009b;Karapetyan et al 2013;Kim et al 2012;Ratajczak et al 2010), an action that is also associated to inflammation. Utilizing a combination of pharmacological and molecular approaches, Barth and co-coworkers demonstrated that in human neuroblastoma cells, CerK activity was strictly required for activation of various oxidoreductases, including reactive oxygen species (ROS) producing NADPH oxidase (NOX), cyclooxygenase (COX), and 5-lipooxygenase (5-LOX), which are enzymes involved in pro-inflammatory processes (Barth et al 2012). The latter study also showed that activation of CerK caused cPLA2 activation and subsequent eicosanoid biosynthesis and that elimination of CerK rescued neuronal viability in the presence of pro-inflammatory TNF-a.…”
Section: Pathophysiological Relevancementioning
confidence: 99%